Consumer reporting of suspected adverse drug reactions: modelling the acceptance of mobile phone caller tunes to raise awareness. Issue 1 (14th November 2019) - Appiah, Bernard; Yoshikawa, Aya; Asamoah‐Akuoko, Lucy; Anum, David Anidaso; Kretchy, Irene Akwo; Samman, Elfreda; Goulart, Ana; Nwokike, Jude; Dodoo, Alexander N. O.; Darko, Delese Mimi; Rene, Antonio
Abstract: Objectives: Our main aim was to identify the factors that may influence consumers' acceptance of mobile phone caller tunes to increase awareness of consumer reporting of suspected adverse drug reactions (ADRs). Mobile phone caller tunes — the songs or messages callers hear — are popular in Africa and Asia but have not been used to aid reporting of adverse drug reactions (ADRs). We also aimed to evaluate the psychometric properties of a survey instrument adapted for caller tunes and ADRs. Methods: A cross‐sectional survey based on the technology acceptance model (TAM) was conducted among 486 non‐ADR‐themed caller tune users and 470 mobile phone users with no caller tunes in Accra, Ghana. Participants were purposively recruited from voluntary blood donation sites. After testing the validity and reliability of TAM constructs, a structural equation modelling approach was used to evaluate the factors that could influence the acceptance of caller tunes for increasing awareness of consumer reporting of ADRs. Key findings: Perceived usefulness and perceived ease of use had significant positive effects on consumers' acceptance of caller tunes for increasing awareness of consumer reporting of ADRs. However, whereas free of cost had significant positive effects on the acceptance of caller tunes among those with non‐ADR‐themed caller tunes ( β  = 0.15, P  = 0.006), it was not so for those lacking caller tunes ( β  = 0.05, P  = 0.229). The survey instrument met acceptable validity and reliability criteria. Conclusions: Our findings show that consumers would generally accept caller tunes on ADRs — if created — to aid consumer reporting of suspected ADRs, but there are research and practice considerations.